2021
DOI: 10.38035/jlph.v1i2.66
|View full text |Cite
|
Sign up to set email alerts
|

Online Shopping Behavior Model: Determining the Factors Affecting Repurchase Intention

Abstract: The growth of digital marketing technology is increasingly being used by e-commerce players in offering each particular product or service. The convenience and perceived benefits in the context of online shopping behavior create new competitors that are increasingly innovative and competitive. This phenomenon is important to study and analyze the dominant factors in influencing repurchase intention, because e-commerce players make repurchase intention factor a determining factor in business continuity. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Another study by Thaichon and Quach (2015) examined how marketing communications could affect repurchase intention by enhancing customer satisfaction, trust, and value perception, finding that brand trust significantly impacts this process. In the study by Nofrialdi (2021), it was shown that e-commerce players see repurchase intention as a decisive factor in business continuity and how e-trust affects repurchase intention, with brand trust playing a significant role by reducing perceived risks and thereby increasing repurchase intentions. The study by Laeequddin et al (2019) found that brand trust and brand risk have similar perspectives in terms of brand characteristics, brand rationality, and brand loyalty.…”
Section: H2mentioning
confidence: 99%
“…Another study by Thaichon and Quach (2015) examined how marketing communications could affect repurchase intention by enhancing customer satisfaction, trust, and value perception, finding that brand trust significantly impacts this process. In the study by Nofrialdi (2021), it was shown that e-commerce players see repurchase intention as a decisive factor in business continuity and how e-trust affects repurchase intention, with brand trust playing a significant role by reducing perceived risks and thereby increasing repurchase intentions. The study by Laeequddin et al (2019) found that brand trust and brand risk have similar perspectives in terms of brand characteristics, brand rationality, and brand loyalty.…”
Section: H2mentioning
confidence: 99%
“…Based on various previous studies, there are many factors that influence repurchase intention such as e-trust, E-Wom, Hedonic value, satisfaction, etc. [6]. Moderating factors are factors that influence or change the relationship between two other variables in a study.…”
Section: Figure 1 E-commerce Users In Indonesiamentioning
confidence: 99%
“…Due to the large number of repurchase intention models that have been developed, there is no definite model for the repurchase intention model. Therefore, it is necessary to conduct a literature review to build a proposed model and obtain an empirical model for further model development [6].…”
Section: Figure 1 E-commerce Users In Indonesiamentioning
confidence: 99%
“…Based on the problem formulation, theoretical studies, previous research and discussion of the influence between variables, the conceptual framework is obtained as follows: , (Nofrialdi, 2021), (E. B. Saputra et al, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%